2012
DOI: 10.1007/s12298-012-0130-x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of somatic embryogenesis in gum arabic tree [Acacia senegal (L.) Willd.]

Abstract: Factors affecting somatic embryogenesis from immature cotyledon of gum arabic tree [Acacia senegal (L.) Willd.] were investigated. Induction of somatic embryogenesis was influenced by plant growth regulator concentrations and addition of amino acids in medium. Best induction of somatic embryogenesis was obtained on MS medium supplemented with 0.45 μM 2, 4-D, 2.32 μM Kin and 15 mM L-glutamine. L-glutamine plays a significant role in the maturation of somatic embryos and most of embryos attained maturity only on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Rathore et al [51] reported that L-glutamine stimulated the maturation of Acacia senegal somatic embryos and reduced reduced embryo abnormalities. Rai et al [52] found that 0.68 mM of glutamine increased maturation percentage of Psidium guajava somatic embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Rathore et al [51] reported that L-glutamine stimulated the maturation of Acacia senegal somatic embryos and reduced reduced embryo abnormalities. Rai et al [52] found that 0.68 mM of glutamine increased maturation percentage of Psidium guajava somatic embryos.…”
Section: Discussionmentioning
confidence: 99%
“…(Kong et al, 2012), Acacia senegal (L.) Willd. (Rathore et al, 2012), Cassia angustifolia (Parveen & Shahzad, 2014). These explants are more proficient for somatic embryo induction, metabolically and biochemically, due to presence of milky white content in immature cotyledons of neem (Gairi & Rashid, 2005).…”
Section: Somatic Embryogenesismentioning
confidence: 99%
“…Furthermore, the surface sterilization of A. auriculiformis had many procedures, the explant was soaked in 0.1% Benlate (fungicide) combination with 1% Boric acid for 24 hours before sterilized with 0.1% HgCl2 for 10 minutes (first sterilization) and 10% Clorox ® for 5 minutes (second sterilization). Although, mercuric chloride is highly antimicrobial, with action against both bacteria and fungi, it should be used at 0.05 -0.1% for 5-10 minutes (Rathore et al, 2012;Banerjee, 2013;Monteuuis et al, 2013;Nagashree et al, 2015). The sterilization studies of Acacia sp.…”
Section: Surface Sterilization Techniquementioning
confidence: 99%